House renovation / Nur Nisa Syafiqah Nasir - Nasir, Nur Nisa Syafiqah (Universiti Teknologi MARA UiTM,Perak, 2022)
House renovation is to return something to a good state of repair or upgrading to something new. It is typically are done for either commercial or residential. In this case, it was done at residential house. The aim of this study is to discover the construction for house renovation for a residential building. The main objective of this report is to identify the methods of house renovation process, to determine the time of house renovation process and to identify the problems and solution in house renovation process. Methodology for the case study technique has been used is by three methods which are observation, interviews, and document review. During the construction for this project, all data was recorded with explanations from supervisor, contractor. As a result, it was determined that contractors must prioritize housing renovations. Lastly, the writer hopes that this report has achieve the objectives related to the house renovation process that is discussed.